Effect Of Annealing Treatments On Normal State Resistivity Of Yba2(cu1-xtix)3oy Superconductor In Bipolaron Model - Mani Kongnine, D.; Hamrita, A.; Napo, K. (University of Eloued جامعة الوادي, 2016)
Samples of YBa2(Cu1-xTix)3Oy superconductor with x=0.00 , 0.01, 0.03 have been prepared by solide state reaction method. The effect of annealing treatments on normal electrical resistivity has been done using the bipolaron model. The results of this study show the increase of localized charge when the dopant content increases and the reduction of this localization with annealing treatment.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 03
Keywords: YBa2(Cu1-xTix)3Oy superconductor, normal state, bipolaron